2022
DOI: 10.1097/sla.0000000000005407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjuvant Steroid Therapy in Type 3 Biliary Atresia

Abstract: Objective: To evaluate the efficacy and side effects of additional postoperative steroid therapy for type 3 BA versus the current routine care. Summary Background Data: Whether steroid therapy post-Kasai portoen-terostomy improves the outcomes of BA remains controversial. Clinical evidence from 2 randomized trials in the UK and USA do not support the routine use of steroid in the treatment of BA. Methods: In this open-label randomized controlled trial, patients with type 3 BA were randomized to routine pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Bilirubin levels every two weeks of therapy 4842 atresia patients after KPE may provide a better result than those who are not administered. 17,18 However, there are no studies regarding the efficacy of administering steroids before KPE, especially when cholestasis develops in young infants.…”
Section: Discussionmentioning
confidence: 99%
“…Bilirubin levels every two weeks of therapy 4842 atresia patients after KPE may provide a better result than those who are not administered. 17,18 However, there are no studies regarding the efficacy of administering steroids before KPE, especially when cholestasis develops in young infants.…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, the use of steroids is widely adopted for its anti-inflammatory effect and promotion of bile flow. A recent RCT and meta-analysis both confirmed that postoperative adjuvant steroid therapy improved bile drainage and native liver survival 161 , 162 . Recurrent cholangitis is another significant factor which negatively affects native liver survival.…”
Section: Hepatobiliarymentioning
confidence: 92%